Colonic Motility and Jejunal Vagal Afferent Firing Rates Are Decreased in Aged Adult Male Mice and Can Be Restored by an Aminosterol - West, Christine L.; Amin, Jessica Y.; Farhin, Sohana; Stanisz, Andrew M.; Mao, Yu-Kang; Kunze, Wolfgang A. (Frontiers in Neuroscience, 2019)
There is a general decline in gastrointestinal function in old age including decreased intestinal motility, sensory signaling, and afferent sensitivity. There is also increased prevalence of significant constipation in aged populations. We hypothesized this may be linked to reduced colonic motility and alterations in vagal-gut-brain sensory signaling. Using in vitro preparations from young (3 months) and old (18-24 months) male CD1 mice we report functional age-related differences in colonic motility and jejunal mesenteric afferent firing. Furthermore, we tested the effect of the aminosterol squalamine on colonic motility and jejunal vagal firing rate. Old mice had significantly reduced velocity of colonic migrating motor complexes (MMC) by 27% compared to young mice (p = 0.0161). Intraluminal squalamine increased colonic MMC velocity by 31% in old mice (p = 0.0150), which also had significantly reduced mesenteric afferent single-unit firing rates from the jejunum by 51% (p < 0.0001). The jejunal vagal afferent firing rate was reduced in aged mice by 62% (p = 0.0004). While the time to peak response to squalamine was longer in old mice compared to young mice (18.82 ± 1.37 min vs. 12.95 ± 0.99 min; p = 0.0182), it significantly increased vagal afferent firing rate by 36% and 56% in young and old mice, respectively (p = 0.0006, p = 0.0013). Our results show for the first time that the jejunal vagal afferent firing rate is reduced in aged-mice. They also suggest that there is translational potential for the therapeutic use of squalamine in the treatment of age-related constipation and dysmotility.